2020
DOI: 10.1186/s12876-020-01434-5
|View full text |Cite
|
Sign up to set email alerts
|

IgA, albumin, and eosinopenia as early indicators of cytomegalovirus infection in patients with acute ulcerative colitis

Abstract: Background: Cytomegalovirus (CMV) infection can significantly complicate and worsen the condition of acute severe ulcerative colitis (UC) patients. We aimed to explore the predictive risk factors to prevent and identify CMV infection at an early stage in acute UC patients. Methods: A total of 115 moderate-to-severe active UC patients from 17 hospitals throughout China were enrolled. Active CMV infection was diagnosed by one of the following: CMV pp65 antigens, CMV IgM antibodies or CMV DNA. We identified the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The prognostic value of low serum albumin levels has been demonstrated not only for the development and complications of acute viral, bacterial, and fungal infections [ 95 ], but also for infectious complications in chronic conditions including malignant diseases [ 66 , 96 ], chronic inflammatory diseases [ 97 , 98 ], diabetes [ 95 ], hemodialysis [ 99 ], and solid organ transplantation [ 100 ]. In chronic infectious diseases, hypoalbuminemia is associated with disease reactivation/recurrence and secondary infections [ 101 , 102 , 103 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…The prognostic value of low serum albumin levels has been demonstrated not only for the development and complications of acute viral, bacterial, and fungal infections [ 95 ], but also for infectious complications in chronic conditions including malignant diseases [ 66 , 96 ], chronic inflammatory diseases [ 97 , 98 ], diabetes [ 95 ], hemodialysis [ 99 ], and solid organ transplantation [ 100 ]. In chronic infectious diseases, hypoalbuminemia is associated with disease reactivation/recurrence and secondary infections [ 101 , 102 , 103 ].…”
Section: Hypoalbuminemia and Prognosis In Infectionsmentioning
confidence: 99%
“…According to our previous study, PTIP contributes to the establishment of steady-state IgG and IgM [10]. Anticommensal IgG activates the FcγR receptor, leading to IL-1b production and aggravation of UC [6]; an increase in IgG levels was observed in the intestinal mucosa from UC patients [20]. However, the function of natural IgM and IgG antibodies in UC is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Although some studies have shown a correlation between serum albumin levels and HCMV infection, to the best of our knowledge, this is the first report of a significant association with a specific gN genotype. 28 The results may provide a reference for the exploration of laboratory biomarkers for HCMV infection in different gN genotypes and the assessment of the value of the application of HCMV gN genotype testing.…”
Section: Discussionmentioning
confidence: 99%